Power Grid Synchronous Detection Based on Voltage and Frequency - Ahmad Khairi, Muhammad Aiman Adam; Salimin, Suriana (Journal of Electronic Voltage and Application, 2025)
The power grid system is a complex electrical network that supply electricity from power generation to consumers. Required the variation of voltage and frequency are maintained within the normative limits. The aim of this research is to design a circuit model that simulate a power grid synchronous system using Proteus 8.17 software. This research had designed and built a model that can detect grid condition based on voltage and frequency variation. Arduino UNO microcontroller had been used in this research to control the overall operation flow. The functionality of the model had been examined through software simulation testing. Six different conditions had been set to test the functionality of the model. The assigned conditions include Normal Voltage (between 207V and 253V), Under Voltage (<207V), Over Voltage (>253V), Normal Frequency (between 49.5Hz and 50.5Hz), Under Frequency (<49.5Hz) and Over Frequency (>50.5Hz). Overall, the developed model in simulation using Proteus 8.17 software had a accuracy when detecting grid based on over/under voltage and over/under frequency variation.